Energy harvesting from coupled bending-twisting oscillations in carbon-fibre reinforced polymer laminates. (July 2018) - Xie, Mengying; Zhang, Yan; Kraśny, Marcin J.; Rhead, Andrew; Bowen, Chris; Arafa, Mustafa
Highlights: First demonstration of laminated beam with bend-twist coupling for energy harvesting. Unique approach to tune the frequency response of the resonant harvesting system. Novel laminate structure and model tuned to provide a broader-band energy harvester. Abstract: The energy harvesting capability of resonant harvesting structures, such as piezoelectric cantilever beams, can be improved by utilizing coupled oscillations that generate favourable strain mode distributions. In this work, we present the first demonstration of the use of a laminated carbon fibre reinforced polymer to create cantilever beams that undergo coupled bending-twisting oscillations for energy harvesting applications. Piezoelectric layers that operate in bending and shear mode are attached to the bend-twist coupled beam surface at locations of maximum bending and torsional strains in the first mode of vibration to fully exploit the strain distribution along the beam. Modelling of this new bend-twist harvesting system is presented, which compares favourably with experimental results. It is demonstrated that the variety of bend and torsional modes of the harvesters can be utilized to create a harvester that operates over a wider range of frequencies and such multi-modal device architectures provides a unique approach to tune the frequency response of resonant harvesting systems.